Forging new directions in physics education in Australian universities. - Kirkup, Les; Sharma, Manjula (Australian Learning and Teaching Council, 2009)
Report from a project that was concerned with physics education in Australian universities. The researchers aimed to illuminate what constitutes good practice in physics service teaching and to identify and disseminate such practice. They aimed to investigate effective undergraduate laboratory learning environments and engage the community in developing sustainable research-based teaching practices. The third area, graduates in the workforce, is an on-going issue as course designers act to meet the challenge of aligning graduate attributes with employer expectations and providing valid employment information to students. The researchers aimed to identify graduate destinations and employer expectations and explore the suitability of current course learning outcomes, content, structures and learning activities. [Executive summary, ed]